Proyecto para la creación de una empresa de venta de brownies ¨sweet brownie¨ en la ciudad de Santa Marta - Caceres Jimenez, Daniel Andres; Serna Sanchez, Maria Camila (Universidad Antonio Nariño, 2021)
Propia